The 9th International Conference "Environmental Engineering 2014" 2014
DOI: 10.3846/enviro.2014.116
|View full text |Cite
|
Sign up to set email alerts
|

Operational study of roundabouts and signal-controlled intersections in Kaunas City

Abstract: Researchers and practitioners often discuss which types of junctions are more efficient in urban territories. Consequently, a proper decision is important in order to minimize the costs of infrastructure for users and government. The aim of the study is to assess and compare operation of roundabouts and signal-controlled intersections under various traffic conditions. The study is based on traffic measurements and data about road accidents. Efficiency of operation is calculated and compared, proposals are give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Most of the large roundabouts in Vilnius were listed as black spots in 2014 (Transport Excellence Agency, 2014). However, it should be noted that large roundabouts are problematic from the point of view of traffic safety also in other larger cities of Lithuania, i.e., Kaunas or Klaipėda (Dumbliauskas, Grigonis, & Barauskas, 2014;Sivilevičius, Paliulis, Klibavičius, & Palevičius, 2015). Black spot is a 500 m stretch of road or street with at least 4 fatalities or injuries in 4 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the large roundabouts in Vilnius were listed as black spots in 2014 (Transport Excellence Agency, 2014). However, it should be noted that large roundabouts are problematic from the point of view of traffic safety also in other larger cities of Lithuania, i.e., Kaunas or Klaipėda (Dumbliauskas, Grigonis, & Barauskas, 2014;Sivilevičius, Paliulis, Klibavičius, & Palevičius, 2015). Black spot is a 500 m stretch of road or street with at least 4 fatalities or injuries in 4 years.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical and case studies (Pratelli, Sechi, & Roy Souleyrette, 2018;Wan, Chen, & Du, 2019) show that continuous and gradual improvement of a guide sign system for roundabouts improve drivers' sense of direction and it is beneficial to improve the safety and efficiency of the roundabout. Gallelli & Vaiana (2019) and Gallelli, Iuele, & Vaiana (2016) highlight that the conversion of the existing roundabout into a virtual turbo roundabout determines an increase in capacity together with a minimization of the queue lengths and potentially reduces the number of conflicts. The research by Hong Kong Transport Department (Wong et al, 2012) related to a spiral-marking system on four roundabouts indicated that there were marginal decreases in potential conflicts on medium-sized roundabouts with relatively low traffic intensity.…”
Section: Introductionmentioning
confidence: 99%